Chemical Constituents and Biological Activites of Selected Cinnamomum Species (Lauraceace) and Melicope Cf. Hookeri T.G. Hartley (Rutaceae - Mohamad Ali, Nor Azah (2004)
The essential oils of nine Cinnamomum species (C, sintoc, C. pubescens, C. impressiscostaturn, C. subavenium, C, microphyllum, C. scortechinii, C. rhyncophyllum, C. aureofulvum and C. verum) were investigated by means of gas chromatography (GC) and combination of gas chromatography/mass spectrometer (GUMS). The chemical components of the essential oils (leaf, stem bark and twig oils) were identified by co-chromatography with authentic samples on three columns of different polarity, comparison with Kovats retention indices, capillary GUMS and proton NMR on selected isolated components. The essential oils were made up of one, two or all three of the following class of compounds; monoterpenes and sesquiterpenoids, phenylpropanoids and benzyl esters. Some of the chemical components observed in the oils are (E)-methyl cinnamate, safrole, benzyl benzoate, linalool, terpinen-4-01 and camphor which are commercially important chemicals in the flavour and pharmaceutical industries. The distribution and occurrences of be used as a chemotaxonomic marker for species identification. Cinnamomum species (C. impressicostatum, C. pubescens, C. microphyllum) and Melicope cf. hookeri were selected for a study of their chemical constituents and biological properties. All of these species have not been reported previously on their chemical constituents. Phytochemical analysis of the bark and stem parts of C. impressicostatum yielded safrole (IS), (@-methyl cinnamate (17), (apiperonylprop- 2-enal (1 16), cinnamic acid (1 17) and P-sitosterol (1 18). Similar analysis on the bark of C. pubescens also afforded safrole (IS), (@-methyl cinnamate (17), (E)-piperonylprop-2-enal (1 16) and P-sitosterol (1 18) as well as (E)- piperonylprop-2-en01 (119). Antimicrobial test using the disc diffusion method showed that the chloroform and the hexane extract of the two species contained almost solely (8-methyl cinnamate, which were active against fungus. The presence of (Q- piperonyl-2-enal (1 16) and (Q-piperonylprop-2-en01 (1 19) were reported for the first time from the genus Cinnamomum. Phytochemical investigation on the stem and bark of Cinnamomum microphyllum resulted in the isolation of a coumarin; scoparone (120), benzyl benzoate (4), Psitosterol (118) and mixtures of pinoresinol-type lignans; pinoresinol (121), syringaresinol (37) and medioresinol (122). The lignan mixture was found to possess significant antioxidant activity against three antioxidant a autooxidation of linoleic acid, xanthinelxanthine oxidase superoxide scavenging assay and DPPH radical scavenging activity. Phytochemical investigation on the leaves and bark of Melicope cf. hookeri T.G. Hartley resulted in the isolation of three flavonoids, two coumarins and sterols. The three flavonoids; ayanin (57), ombuin (123) and kumatakenin (124) together with Psitosterol (1 18) were isolated from the leaves. The bark extract afforded ayanin (57), P-sitosterol (lls), urnbelliferone (102) and scopoletin (125). Crude extracts of M. cf. hookeri were screened for antimicrobial activity, antioxidant activity and TPAinduced ear oedema assay. The extracts failed to show significant antimicrobial or antioxidant activity. However, the leaf ethyl acetate extract showed strong antiinflammatory activity with the chloroform extract (95%) and methanol extract (92%) showing the highest inhibitions as compared to the petroleum ether extract (70%). The presence of flavonoid compounds in the species probably contribute to the antiinflammatory activity of the plant extracts